Copy the Master Strategy with Synectic Model Assisted by Puzzle Media on Motivation and Learning Outcomes in Writing Imaginative Stories - Sukarman, Lufi Afita Kardina; Hartono; Ari Kusmiatun (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Students' low writing skills are generally caused by suboptimal teaching methods implemented by teachers. This study aims to analyze the impact of the "Copy the Master" learning strategy combined with the synectics model supported by puzzle media on students' motivation and learning outcomes in writing imaginative stories. The research was conducted on seventh-grade students using a quasi-experimental method with a posttest-only control group design. The study involved two classes: a control class and an experimental class. The population consisted of seventh-grade students. Learning motivation data were collected using a questionnaire, while students’ learning outcomes were gathered through an objective (essay) test. The results showed a difference in learning motivation and outcomes after applying the "Copy the Master" strategy with the synectics model and puzzle media. Data analysis using MANOVA and hypothesis testing revealed a significant difference between the two groups, with the experimental group achieving an average learning outcome score of 81.21 compared to 71.00 for the control group, and an average motivation score of 75.85 compared to 71.07 for the control group. These findings indicate that the "Copy the Master" strategy with the synectics model supported by puzzle media is effective in enhancing motivation and the ability to write imaginative stories. The implication of this study is that teachers should be able to select and implement appropriate models and strategies in the learning process to create active, innovative, and meaningful learning experiences.